THE EFFECTIVENESS OF BIOCHAR APPLICATION IN THE REFORESTATION OF POST-MINING LANDS IN EAST KALIMANTAN - Hakim, Dani Lukman; Kowalska, Marta; Gibbons, Theresa (Journal of Selvicoltura Asean, 2025)
Large-scale mining in East Kalimantan leaves severely degraded lands characterized by extreme acidity and chemical toxicity, which critically impede mandatory reforestation efforts often exacerbated by the transient nature of conventional amendments. This study aimed to rigorously quantify the effectiveness of varying biochar dosages on the chemical stabilization of post-mining spoil and the subsequent survival and growth of local pioneer tree species, with the goal of developing an Optimal Biochar Application Protocol. A multi-factorial, randomized complete block design experiment was conducted over 24 months, comparing three biochar dosages (up to 10 \text{ t/ha}) against control and mineral fertilizer plots, supported by a Life-Cycle Cost Analysis (LCCA). Results demonstrated that the optimal dosage (10 \text{ t/ha}) neutralized the spoil’s \text{pH} from 4.0 to 6.5, doubled the Cation Exchange Capacity (\text{CEC}), and achieved a 92% plant survival rate (versus 48% in control plots). The ecologically superior biochar treatment also proved to be 35% more cost-effective than repetitive mineral fertilization over the study period. The research concludes that biochar provides the durable, holistic, and cost-effective solution, successfully addressing the root cause of reclamation failure. The findings validate the Optimal Biochar Application Protocol, compelling a necessary shift toward sustainable, carbon-sequestering reclamation practices.